Efficacy of oseltamivir compared with zanamivir in COPD patients with seasonal influenza virus infection: a randomized controlled trial - Li,Min (2021)
Influenza viruses exacerbate chronic obstructive pulmonary disease (COPD) with considerable morbidity and mortality. Zanamivir and oseltamivir are effective in treating influenza. However, their efficacy in relieving influenza symptoms in COPD patients remains unknown, with the lack of controlled trials in this subject. Therefore, we conducted this randomized controlled trial to investigate the clinical efficacy of both interventions in this population. Patients were allocated to two groups (80 patients each): oseltamivir (OSELTA) and zanamivir (ZANA) groups. Oseltamivir (75 mg) was orally administered twice daily for 5 days, while zanamivir (10 mg) was inhaled twice daily for 5 days. Clinical parameters including body temperature, influenza symptoms (i.e., sore throat, cough, etc.), and serial blood tests were recorded on days 1, 3, and 7. We analyzed primary (changes in body temperature) and secondary outcomes (changes in non-specific symptoms) using the pre-protocol and intention-to-treat analyses. Differences between groups were assessed using t-test. Oseltamivir and zanamivir significantly reduced body temperature on the 3rd day after treatment; however, the number of patients who reported clinical improvement in influenza-like symptoms was significantly higher in the OSELTA group compared to the ZANA group on days 3 (85 vs 68.8%, P=0.015) and 7 (97.5 vs 83.8%, P=0.003). However, no significant changes in hematological (white blood cells and its subtypes) and inflammatory (C-reactive protein) parameters were noted (P>0.05). Our results suggested that oseltamivir and zanamivir are effective in reducing body temperature, while oseltamivir led to better clinical improvement regarding influenza-like symptoms in patients with COPD.